Impact of various factors on stock-induced food waste in Indian weddings: A system dynamics approach. Issue 1 (5th February 2018) - Sharma, Neeta; Vrat, Prem
Abstract : Purpose: Weddings in India have become more extravagant in recent years. The ostentation goes well with the food also. Hundreds of varieties and great stock of food served making it a wasteful affair which would lead to the unsustainable demand for the natural resources. The purpose of this paper is to link the stock-induced consumption phenomenon with food waste generation in Indian weddings. Design/methodology/approach: This study begins with the identification of the factors which would be responsible to make the food consumption stock-induced. A system dynamics (SD) model is developed using SD software STELLA (version 10.0) to assess the amount of stock-induced food waste. The impact of the factors on this waste is analyzed and estimation is made about the financial implications of this waste. Different scenarios have been analyzed to arrive at a most desirable scenario in the Indian context. Finally, the paper provides the recommendations for managerial implications to prevent the potential disastrous consequences of this waste. Findings: A rigorous simulation analysis was conducted for different food-serving scenarios. The outcome of SD analysis shows that an enormous amount of food is wasted in the form of stock-induced consumption and dustbin waste. Impact analysis of factors on waste generation reveals that food wastage in marriages is entirely a behavioral phenomenon and can be controlled by exercising self and enforced behavioral control measures. Waste cost estimation gives an insight about the severity of the topic for policy making. Social implications: The study has a very high social relevance and facilitates decision makers to take required actions to mitigate the stock-induced food waste in marriages. The study conducted will encourage the researchers to use SD in analyzing complex systems for quantitative estimations. Originality/value: To the best of the authors' knowledge, this is the first study that analyzes the food waste in Indian weddings in relation with the huge stock served using SD. The study provides valuable insights in the direction to make the country food secure.